“The Environmental Impacts of Tourism Industry: A Case Study of Jammu and Kashmir” - Zulufqar Manzoor; Dr. Rather Tajamul Islam (Genius Journals, 2021)
Tourism industry is one of the largest and fastest growing sectors in the world economy. Tourism now has become most popular global leisure activity. Jammu and Kashmir also known as” Paradise on Earth” possess its rich cultural heritage, world famous pilgrimage destinations, rich flora and fauna, wild animal's sanctuaries, snow clad mountains, and scenic sports etc. which attract tourists from all over the world. Although, tourism plays a vital role in the upliftment of a region, by creating employment opportunities and improving infrastructural facilities but it can also have deteriorating impacts on the environment, if not properly managed. The present paper analyses the environmental impacts of tourism in Jammu and Kashmir. The present study is based on secondary data, been collected from various official sources. It is found from the study that tourism has the potential to create beneficial effects on the environment by contributing to environmental protection and conservation. It is a way to raise awareness of environmental values and it can serve as a tool to finance protection of natural areas and increase their economic importance. But at the same time, the increasing pressure of tourism has caused the problems of over constructions of hotels, deforestation, air pollution, solid waste, water pollution etc. Indiscriminate throwing of municipal solid waste into rivers is common practice in these tourist destinations, as result river water is continuously getting polluted. Therefore, tourism needs to be planned, administered and taken in an environmentally sustainable, socially favorable and economically feasible way to shun its destructive impacts.
Keywords: Development; Economy; Environment; Impacts